Development of time-temperature responsive Antimicrobial Hydrocolloid Biopolymer for quality maintenance indicators of fresh produce (fruits) - Kamra, Aishwarya (My University, 2019)
The present study attempted to characterize and apply the intrinsic antimicrobial properties of exopolymers produced by Lactic acid bacteria in extending the shelf stability of fruits. A total of 24 bacterial isolates were chosen based on their ability to produce expolysaccharides, of these two isolates namely, Lactobacillus acidophilus (L1) and Lactobacillus fermentum (F4) were finally selected. Exoploymers were produced in midlog phase with a yield of 104 and 84mg/g dry cell mass respectively. The purified exopolymers were determined for their surface morphology using SEM and EDS spectrum. Chemical and FTIR analysis indicated the presence of carboxyl, esters, hydroxyl, and sulphate groups; whereas proteins and sugars could be detected in the purified biopolymers. Both exopolymers were stable at ambient temperature for over 30 days. The isolated polymers demonstrated antimicrobial activities against fungal pathogen (Penicillium sp) isolated from infected pomegranates (Punica granata) in different potencies under in vitro conditions. In order to understand the applicability of the polymers, artificially contaminated fruits (pomegranate) with the respective fungal pathogen were used along with controls and polymers encapsulated with redox dye were coated on the selected fruit (pomegranate). Storage of experimental fruits at different temperatures i.e. 4◦C, 28◦C and 40◦C. exhibited prominent colour changes reflecting the growth status and thus spoilage course of the pathogen. The maximum colour change was observed at 28◦C. A simple process of colour based measurement of was adopted using Adobe illustrator software. The colour intensity variation of the peel of pomegranate was used to develop shade cards. The producer strains were ascertained to possess probiotic properties ascribing them safety for further applications. Results of this study indicate an interesting possibility of coating fruits for the indication of freshness during postharvest handling.
MSc Biotechnology Thesis
Keywords: Exopolymers; Redox dye; Probiotics; Pomegranate; Fungus